Windows Server® 2008 R2 administration : instant reference - Hester, Matthew, 1971-; Henley, Chris (Serious skills., 2010)
All your Windows Server 2008 R2 questions answered--on the spot! Get up to speed on the new features of Windows Server 2008 R2 with this indispensableguide. Designed for busy IT professionals, it's the perfect go-to resource for quick answers and real-world solutions as you administer the new server OS. You'll find easy-to-read lists, quick-reference tables, helpful thumb tabs, and much more in a handy, compact format that puts the information you need at your fingertips. Topics include: Getting started and adding roles and functionality Automating tasks Managing users, groups, directories, and the centralized desktop Handling folder security, disk management, storage, backup, and recovery Monitoring and maintaining web servers Troubleshooting IP and managing remote access Doing performance tuning and maintaining virtual servers.